Cloning of Genomic DNA Flanking Transposon in the Nonpathogenic Mutant of Xanthomonas axonopodis pv. glycines M715 - RUSMANA, ALINA AKHDIYA; SUWANTO, ANTONIUS; TJAHJONO, BUDI (HAYATI Journal of Biosciences, 2009)
The objective of this work is to clone flanking DNA derived from Tn-5 mutagenesis of wild type strain Xanthomonas axonopodis pv. glycines as first step to clone and to identify the gene involved in pathogenicity mechanism. We have localized the flanking DNA fragment from a nonpathogenic mutant of Xag M715. Southern hybridization analysis using 2.8 kb EcoRI from pYR103 as a probe showed that the fragment is located within 2.0 kb PstI fragment. A 0.7 kb flanking DNA was amplified using inverse PCR technique, and inserted into pGEM-T Easy vector generating a 3.7 kb recombinant plasmid (pAA01). Southern hybridization analysis of the wild type (YR32) with pAA01 as a probe indicated a hybridization signal located at approximately 3.0 kb PstI fragment. DNA sequence analysis revealed that the DNA fragment has a 64% identity to a vir gene of Bacillus anthracis.